TRANSFORMASI MEDIA CETAK SUARA MERDEKA MENUJU PLATFORM DIGITAL - Lutfi Andriyani Lutfi Andriyani; Dedy Riyadin Saputro (Lembaga Sepercenter, 2026)
The development of information and communication technology has driven significant changes in the mass media industry, particularly print media. The decline in newspaper circulation and the shift in people's information consumption patterns to digital platforms have required media companies to adapt. This study aims to analyze the transformation process of Suara Merdeka print media to a digital platform, the strategies implemented, and the challenges faced in the process. The research method used is a qualitative approach with literature study and descriptive analysis of the development of media digitalization. The results show that the transformation was carried out through the development of an online news portal, optimization of social media, editorial convergence, and innovation of a digital-based business model. This transformation has become an important strategy in maintaining existence and competitiveness in the digital era.